Explosive Performance Properties of Erythritol Tetranitrate (ETN). Issue 4 (5th June 2015) - Manner, Virginia W.; Preston, Daniel N.; Tappan, Bryce C.; Sanders, V. Eric; Brown, Geoff W.; Hartline, Ernie; Jensen, Brian
Abstract Erythritol tetranitrate (ETN) is a melt‐castable explosive with impressive performance, similar to the well‐known related nitrate ester, pentaerythritol tetranitrate (PETN). Though ETN has been known since 1849, its properties have not been thoroughly investigated. We report here the first 1/2′′ copper cylinder tests of ETN, compared with PETN. We discuss detonation and wall expansion velocity, along with diameter effect information in unconfined rate stick tests. The detonation velocity of ETN is 99 % that of PETN in the same test setup, showing that performance properties are very similar for the two nitrate esters.